Konsolidasi Metodologis Kalender Islam Internasional: Meneladani Intelektual Umar Bin Khattab dan Julius Caesar - Muh Rasywan Syarif; Naif (Jurnal Bimas Islam, 2017)
Efforts to build an international Islamic calendar had been addressed in international scientific seminars since 1393 H / 1973 AD, most recently on 28-30 May 2016/21-23 Syaâ€™ban 1437 H under the theme "Muktamar Tauhid in Takwim al-Islami ad-Dauliâ€ or International Islamic Calendar Unification in Istanbul-Turkey Conference, 2016. This seminar was formed by voting, which is to accept the international Islamic Calendar unification and to reject various forms of the zonal calendar. Nevertheless, this decision does not make the International Islamic calendar automatically applied. Consequently, it is expected the implementation and political authority in utilising it. In this case, the state involvement, Islamic associations, religious institutions, educational institutions and Muslim societies have a pivotal role regarding the development and application of this international Islamic calendar. By using a detailed analytical approach, this paper aims to photograph the steps and tasks of the figure exemplary to consolidate strategy in seeking realisation the international Islamic calendar unification. The results of this study found that the importance of a single authority role such as the OIC to justify and to socialize the International Islamic Calendar implementation for civil, worship, economic, social and other purposes. Upaya membangun Kalender Islam internasional telah dibahas dalam melalui seminar ilmiah internasional sejak 1393 H/1973 AD, terakhir pada 28-30 Mei 2016 1437 Sya'ban M/21-23 H dengan tema "Mukhtamar Tauhid di Takwim al - Islami iklan-Dauli atau ' Kalender Islam Internasional penyatuan di Istanbul Turki (Turki konferensi 2016). Dari seminar ini dihasilkan keputusan, melalui pemungutan suara, yaitu menerima penyatuan Kalender Islam internasional dan menolak berbagai bentuk kalendar zonal. Namun keputusan ini tidak nebjadikan kalender Islam Internasional otomatis diterapkan. Dibutuhkan strategi implementasi dan wewenang politik dalam menerapkannya. Dalam hal ini keterlibatan negara, organisasi Islam, lembaga keagamaan, lembaga pendidikan dan masyarakat muslim sangat penting dalam pengembangan dan penerapan Kalender Islam internasional ini. Dengan menggunakan sebuah pendekatan analitis deskriptif, tulisan ini bertujuan memotret langkah dan peran tokoh teladan mengkonsolidasikan strategi dalam mencari realisasi penyatuan Kalender Islam internasional. Hasil studi ini menemukan bahwa pentingnya peran otoritas tunggal seperti OKI untuk membenarkan dan bersosialisasi pelaksanaan Kalender Islam Internasional untuk kegiatan sipil, ibadah, ekonomi, sosial dan keperluan lainnya.